West Kalimantan Border Development Strategy through Tourism Sector Using Analytic Network Process Method - Dian Anggraeni Rahim (Krisnadwipayana International Journal of Management Studies, 2022)
The development of the border area of West Kalimantan is not only to increase regional income, but furthermore, the aims are to improve people's welfare and reduce regional disparities that result in backwashing the economy. One of the flagship areas in the border area that requires serious attention is tourism development. This research uses ANP (Analytic Network Process) to obtain a tourism development strategy in the border area of West Kalimantan. Nine respondents are development planners. Tourism development strategies in border areas include natural, cultural, and culinary tourism. The problems that arise in the tourism sector are poor infrastructure, lack of promotion, and inadequate transportation for the development of natural tourism. For cultural tourism, the main problem is the lack of maintenance of cultural assets, rarely do festivals and locations are difficult to reach. In comparison, culinary tourism focuses on maintaining guaranteed halalness, having reasonable prices, and maintaining cleanliness. The rater agreement in this study consisted of the consistency index value in the range of 0.02 – 0.09 and Kendall's Coefficient of Concordance of 0.667.